Intangible assets reporting: The case of chemical and pharmaceutical industry in the Czech Republic - Bohušová, Hana; Svoboda, Patrik (Mendelova univerzita v Brně, 2018)
The cost structure of business entities has been changing in the span of time. Costs associated with intangible assets such as software, patents, licenses, copyrights and goodwill became an important item of costs in the recent days. The paper is focused on the evaluation of the share of intangible assets in total assets and the costs associated with intangible assets in business companies operating in the chemical and pharmaceutical industry in the Czech Republic. The analyzed sample of companies represents two groups of business entities: entities preparing financial statements in accordance with IFRS and the entities preparing financial statement according to the Czech Accounting legislation (CAL). The sample covers period after the mandatory implementation of IFRS for listed companies-starting in 2005 and ending in 2015. The aim of this paper is to evaluate the impact of intangible assets reporting methodology using criteria as the share of this category in assets of companies, its structure and its changes over time and to identify possible reasons for this situation. The analysis revealed that there is an increasing tendency in volume of IAs in companies listed in Prague Stock Exchange.
Keywords: CAL; Fixed assets; GDP; Goodwill; IFRS; Intangible assets